Self-Efficacy and Shot Success of Basketball Players - Santua, Raymund Jason P. (Philippine Social Science Journal, 2020)
In the Philippines, basketball is a popular sport, and there are local, provincial, and regional and national competitions (Antolihao, 2010). From urban and rural areas, both public and private institutions, organizations, sectors, different schools province, city, municipality or towns, barangays and every corner of the street or block, Filipinos play basketball even in a small area that can make a small court or half-court and a basketball ring or sometimes a basketball ring without a board (De la Cruz, 2016). A tale or a myth attests to the powerful influence of Filipinos’ sport and a keen interest in basketball and its existence in their archipelagic geography, despite the sport being designed or tailor-made for tall people (Dumaraos, 2016). There are varsity players in colleges who are scholars because of their ability to play this game. The sports career of basketball players goes a long way even when they have graduated from school. They may become professional and paid basketball players later (Sugai, 2010). However, being an expert basketball player requires much practice. Basketball players may be professionally trained or may have started as a backyard player or may have no professional training. There are backyard players who have very high accuracy and precision in shooting, which are part of their genetic characteristics (Perine, 2016). Nevertheless, these genetic characteristics may be enhanced by experience. On the other hand, Ortega, Olmedilla, de Baranda, and Gomez (2009) found that basketball players with high self-efficacy have higher performance or shot success. The success of shooting the ball may depend on the confidence that a person had had when he was shooting. The more confident he has been, the better his chance of being precise in the shooting. This is self-efficacy, confidence, and the effectiveness of achieving success in one’s aim (Perlman, 2018). Hence, the study aimed to describe, compare, and correlate self-efficacy and shot success of basketball players of the Iloilo City Mayor’s Cup.